Deep sequencing of BCR-ABL1 kinase domain mutations in chronic myeloid leukemia patients with resistance to tyrosine kinase inhibitors. Issue 1 (2nd January 2019) - Erbilgin, Yucel; Eskazan, Ahmet Emre; Hatirnaz Ng, Ozden; Salihoglu, Ayse; Elverdi, Tugrul; Firtina, Sinem; Tasar, Orcun; Mercan, Sevcan; Sisko, Sinem; Khodzhaev, Khusan; Ongoren, Seniz; Ar, Muhlis Cem; et al.
Abstract: Tyrosine kinase inhibitor (TKI) therapy is the current treatment of choice for patients with chronic phase chronic myeloid leukemia (CML) leading to rapid and durable hematological as well as molecular responses. However, emergence of resistance to TKIs has been the major obstacle to treatment success on long term. In this regard kinase domain mutations are the most common mechanism of therapy failure. In this study, we analyzed peripheral blood samples from 17 CML patients who had developed resistance to various TKIs by using next-generation sequencing parallel to Sanger sequencing. BCR-ABL1 kinase domain mutations have been found in 59% of the cohort. Our results demonstrate that next-generation sequencing results in a higher mutational detection rate than reported with conventional sequencing methodology. Furthermore, it showed the clonal diversity more accurately.